Dinâmica do uso e ocupação da terra associada ao crescimento de processos erosivos lineares e aos aspectos sóciodemograficos e físico-estruturais - Souza, Natália da Costa (Universidade Federal de São Carlos, 2020)
Interdisciplinary researches has emerged in order to understand the multiple causes and consequences resulting from changes in the forms of appropriation of surface. For this reason, it is common to develop analytical approaches that consider spatial, temporal and socio-environmental vulnerability variables as a support for territorial planning. It is possible to prepare previsions of scenarios and prognosis for areas that will present social vulnerability and environmental degradation, providing subsidies for spatial planning and the sustained development of human activities. In this context, the analysis of the association between land use and land cover changes, socio-demographic and physical-structural aspects and the growth of gully erosive processes in Santa Rita do Passa Quatro –SP (Rio Claro, Córrego da Capituva and Bebedouro watershed), between the years 1990 – 2017 is justified. This period is marked by the occupation of urban areas in the region and the consequent intensification of changes in the form of occupation. This study is a possible method of subsidizing actions for planning and monitoring land use and coverage. The main contribution of the research is to assess which social, demographic, physical-structural and environmental dimensions are associated with the dynamics of transforming surface and how they can assist in the modeling of future scenarios for occupying it. The methodological process takes place in 9 procedures, which are: definition of the analysis time series, mapping of the gully erosion processes identified in the study region, analysis of the processes autocorrelation, collection of land use and coverage data, analysis of temporal changes, selection of indicators and explanatory variables and the final proposal for modeling spatial dynamics using the MOLUSCE - QGIS 2.18.0 plugin. As a result, the present research discusses the main classes that suffered oscillations between the years analyzed, the cases of erosion registered during the series and in the transitions that occurred, in addition to exploring how they influence some elements when inserted in the modeling future land use scenarios.
Land change cover dynamics associated with the growth of gully erosive processes and sociodemographic, physical-structural aspects
Keywords: Dinâmica de uso e cobertura da terra; Processos erosivos lineares; Geoinformação; Sistemas de Informaçao Geográfica; Plugin molusce; Land change cover dynamic; Gully erosion; Geoinformation; GIS; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS